Comprehensive Analysis of the Aging Behavior of Nickel-Rich, Silicon-Graphite Lithium-Ion Cells Subject to Varying Temperature and Charging Profiles. Issue 6 (28th June 2021) - Schindler, Markus; Sturm, Johannes; Ludwig, Sebastian; Durdel, Axel; Jossen, Andreas
Abstract : Especially for material combinations incorporating silicon-graphite anodes and nickel-rich cathodes, lifetime and energy density have to be balanced appropriately. In particular, silicon-graphite anodes show increased aging effects due to the extensive volume expansion of silicon and even small variations of its content lead to significant changes in the cell properties because of its large specific capacity. Two batches of the same cell, which differ slightly in their silicon content, were investigated using various charging profiles for a temperature range from 0 °C to 40 °C. The total number of EFC of both cell batches was shown to be strongly dependent on temperature. In addition, cells with reduced silicon content showed EFCs three times higher than their higher silicon counterparts. Contrary to expectations, an extended CV-charging sequence led to an increase in EFC and a decrease in variance. The exclusion of critical voltage ranges shows the most significant influence on both the total of EFC and the variance between the cells. As a result, to increase cell lifetime it is recommended that cells should be preconditioned at low ambient temperatures and extended CV-charging sequences should be considered. If the operational strategy allows the reduction of the upper-voltage-limit, critical voltage areas should be avoided.